Ortografie współczesnego piśmiennictwa śląskojęzycznego - Jaroszewicz, Henryk (Slavia Occidentalis, 2022)
Over the past two decades, Silesian literature has been written in eleven different types of orthography, the most important of which are the classical, neo-Steuer and “slabikŏrzowa” orthographies. Other orthographic proposals, e.g. by D. Dyrda, B. Kallus, P. Kalinowski, H. Kaluza, R. Wencel, did not become popular and were abandoned rather quickly. As a result, contemporary Silesian literature was dominated by the “ślabikŏrzowa” spelling, gaining popularity due to its conservative form and the support of the most essential Silesian publishing houses. However, an obstacle to the complete stabilisation of Silesian orthography is the variant spelling of “ślabikŏrzowa” (“full “ślabikorz” and simplified “ślabikŏrz”) and no detailed, explicative normative works (i.e. orthographic dictionary, grammar).